2014
DOI: 10.1177/1934578x1400900918
|View full text |Cite
|
Sign up to set email alerts
|

Potent SIRT1 Enzyme-stimulating and Anti-glycation Activities of Polymethoxyflavonoids from Kaempferia parviflora

Abstract: The SIRT1 enzyme-stimulating and anti-glycation activities of Kaempferia parviflora extract and its main polymethoxyflavonoids were evaluated in vitro. K. parviflora extract elevated SIRT1 catalytic activity by eight-and 17-fold at 20 g/mL and 100 g/mL, respectively, compared with vehicle only. Two major polymethoxyflavonoids, 3,5,7,3',4'-pentamethoxyflavone (4) and 5,7,4'-trimethoxyflavone (5), were isolated from this extract and are four-and fivefold more potent than resveratrol, hitherto the strongest kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…HTF is one of the major OH-PMFs, existing mainly in the citrus genus such as Citrus sinensis , Citrus mangshanesis , and Citrus clementina , which displayed significant antioxidant activities and showed remarkable inhibition effects on the B16 cell lines at a concentration range from 6.25 to 50 μg/mL [13]. OH-PMFs, the flavonoid subclass in which all or almost hydroxyls are capped by methylation, have drawn more and more attention recently because accumulating evidence has demonstrated that OH-PMFs have many stronger health-promoting biological activities and higher oral bioavailability than their permethoxylated counterparts [14]. OH-PMFs have been proven to exhibit a broad spectrum of biological properties including anti-carcinogenic [15,16], anti-coagulation [17], anti-inflammatory [18,19], and anti-oxidant activities [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…HTF is one of the major OH-PMFs, existing mainly in the citrus genus such as Citrus sinensis , Citrus mangshanesis , and Citrus clementina , which displayed significant antioxidant activities and showed remarkable inhibition effects on the B16 cell lines at a concentration range from 6.25 to 50 μg/mL [13]. OH-PMFs, the flavonoid subclass in which all or almost hydroxyls are capped by methylation, have drawn more and more attention recently because accumulating evidence has demonstrated that OH-PMFs have many stronger health-promoting biological activities and higher oral bioavailability than their permethoxylated counterparts [14]. OH-PMFs have been proven to exhibit a broad spectrum of biological properties including anti-carcinogenic [15,16], anti-coagulation [17], anti-inflammatory [18,19], and anti-oxidant activities [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led to the prevailing model in which SIRT1 imparts many of the benefits of a calorie restriction diet 6971,136 . Additional screens for more potent, soluble and efficacious STACs have been successful 172,173 .…”
Section: Figurementioning
confidence: 99%
“…In 2014, Nakata et al reported that polymethoxyflavonoids from the Thai black ginger Kaempferia parviflora , especially quercetin 3,5,7,3′,4′-pentamethyl ether (KPMF-8), show dramatic activation of SIRT1 activity 19 . However, the legitimacy of KPMF-8 as a direct SIRT1 activator is totally unknown, as the FdL peptide substrate was used in the initial activity assay 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Nakata et al reported that polymethoxyflavonoids from the Thai black ginger Kaempferia parviflora , especially quercetin 3,5,7,3′,4′-pentamethyl ether (KPMF-8), show dramatic activation of SIRT1 activity 19 . However, the legitimacy of KPMF-8 as a direct SIRT1 activator is totally unknown, as the FdL peptide substrate was used in the initial activity assay 19 . In light of skepticism about other controversial STACs, further study is required to determine the followings: (1) whether KPMF-8 directly interacts with SIRT1, (2) whether KPMF-8 activates SIRT1 towards the native substrate, and (3) whether KPMF-8 can penetrate the cell membrane and accelerate intracellular deacetylase activity within the cellular environment.…”
Section: Introductionmentioning
confidence: 99%